Discovery of transcription start, transcription termination and transcript processing sites in Halobacterium salinarum NRC-1 using dRNA-seq - Ibrahim, Amr Galal Abd El-Raheem (2023)
Differential RNA sequencing (dRNA-seq) has been proven to be a valuable tool for studying bacterial and archaeal genomes by identifying transcription start sites (TSS). With the help of statistical analysis, researchers can analyze dRNA-seq reads from treated and untreated libraries based on the activity of the 5-monophosphate dependent terminator RNA exonuclease (TEX). Our study focuses on Halobacterium salinarum NRC-1, a type of extremophilic archaeon that is commonly found in highly saline environments and is a model organism for studying molecular biology and genetics in extreme environments. The objective of our study is to identify and map Alternative Transcription Start Sites (alTSS), Transcript Process Sites (TPS), and Transcription Termination Sites (TTS) using the dRNA-seq data in H. salinarum NRC-1. We modified the TSSAR tool to detect TSSs from dRNA-seq data, assuming that sequencing reads start at the exact position during transcription and follow a Gamma-Poisson distribution. We annotated alTSSs into four types based on the number of dRNA-seq library reads and differences between two main TSS locations. Alternative TSSs have lower RNA reads than primary ones and can have upstream open reading frames, leading to changes in gene regulation output, 5UTR isoform, and gene transcription pausing. Mapping alTSSs allowed us to explain changes in cell response to growth conditions and gene expression across different growth stages. Our findings revealed a significant number of falsely annotated internal transcription start sites (iTSSs) that were redefined as alternative TSSs in previous genome annotations. These alternative TSSs produced different protein isoforms depending on the length of the amino acid chain and the open reading frame. Additionally, alternative TSSs were identified not only in H. salinarum but also in other organisms, suggesting a crucial role in regulating gene expression across various species. Furthermore, we conducted a re-analysis of dRNA-seq data, focusing on non-primary transcripts (monophosphorylated RNAs) instead of the traditional method of enriching for primary transcripts (triphosphorylated RNAs) to identify genome-wide transcript processing sites (TPS) in H. salinarum NRC-1. We also applied this approach to Haloferax volcanii for comparative analysis. Lastly, we used dRNA-seq data to identify hairpin structures and mapped them onto the genome, providing insights into the potential role of transcription termination sites (TTS).